Development of MojiGoiGo!: Adobe Flash Based Learning Media For JLPT Preparation - Krishna Adnyani, Kadek Eva; Satya Hermawan, Gede; Partha Sindu, I Gede (International Journal of Language and Literature, 2018)
This study aims to develop Adobe Flash CS6 "MojiGoiGo!" Based Learning Media for Preparation of Level 4 Japanese Language Proficiency Test (JLPT) for Second Semester Students of the Japanese Language Education Department Ganesha University of Education. This research and development uses the development model of Hannafin and Peck. The data are collected through literature review and questionnaires. The collected data are then analyzed by using quantitative analysis. On the requirement needs assess phase, questioners are given to 32 students of second semester of Japanese Language Education Department. On the design phase, materials and products are designed and then inputted into software. On the develop/implement phase, validation of the content and media experts, individual tests, and group trials are conducted. The results of experts validation and individual trials show that the media are considered excellent, while group trials gave judgment on the category of good and excellent.Â Keywords: research and development, learning media, adobe flash CS6, Japanese-language proficiency test